2017
DOI: 10.1186/s40066-017-0102-z
|View full text |Cite
|
Sign up to set email alerts
|

Is bean really a women’s crop? Men and women’s participation in bean production in Uganda

Abstract: Background: Common bean one of the grain legumes that was traditionally considered a subsistence crop and therefore a woman's crop in Uganda was prioritized for commercialization. This has transformed the crop from being a subsistence crop (food security crop) to a commercial crop with more men engaged in its production. Little is known about the possibility of gender conflicts in production activities as the crop finds market. Methods:The study uses gender-disaggregated survey data from 500 men and 625 women … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(31 citation statements)
references
References 18 publications
(28 reference statements)
1
25
1
Order By: Relevance
“…On this basis, prospective improved pigeonpea seed program in Malawi should prioritise female farmers during dissemination. Second, anecdotal evidence, which has been recently supported by Nakazi et al (2017), has peas that are 'women crops' and less cultivated by male, suggesting that women may not be disadvantaged in terms of access to productive inputs because women face less discrimination in the production process of pigeonpea in Malawi.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On this basis, prospective improved pigeonpea seed program in Malawi should prioritise female farmers during dissemination. Second, anecdotal evidence, which has been recently supported by Nakazi et al (2017), has peas that are 'women crops' and less cultivated by male, suggesting that women may not be disadvantaged in terms of access to productive inputs because women face less discrimination in the production process of pigeonpea in Malawi.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, this study is of importance to Malawian agricultural and gender policies considering the statistical joint report of the UNEP and the World Bank (2015) which reveals that women farmers in Malawi are older by over 5 years on average and also have lower levels of education as compared with male farmers, suggesting that Malawian women are approaching less economic active years with low social and human capital than men. With legumes being considered 'women's crops' by many researchers (Doss 2001;Nakazi et al 2017;Njuki et al 2011), we explore two major leguminous crops in Malawi, namely, groundnuts and pigeonpea, and by doing this, we have been able to provide a better understanding of gender gap in productivity analyses with respect to crop specificity and farm decision-making.…”
mentioning
confidence: 99%
“…Fortunately, this technological barrier is rapidly eroding, but these barriers can also be cultural, not only with respect to changing perceptions of cell phone use solely for communication but also in gendered differences of access, use, and safety for women (Hafkin, 2000). This is critical, given the pivotal role of women in the postharvest value-chain of legumes such as cowpea (Nakazi et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In many countries, certain crops have been loosely categorised as either a 'male crop' or a 'female crop' depending on either the gender of the household head, the owner of the land on which a crop is grown or the gender of the person who keeps the proceeds from crop sales [21]. It has been found that women are more likely to control the production and output of the subsistence crops for home consumption, whereas men may have more decision-making power over the production and output of the household's cash crops [21,28].…”
Section: Introductionmentioning
confidence: 99%